Finding House Dust Mites in 90 Homes in Three Districts of Bogota, Colombia - Poveda , Daniela; Chang , Andrés; Cuadros, Gustavo; Acero, Victor (Spei Domus, 2014)
Introduction: mites are microorganisms found in the common house dust, which in most cases cause respiratory and skin diseases. This has a significant impact on quality of life and turns this issue into a veterinary public health matter, given that house mites are potentially related to having pets. The general objective of this paper is to determine the amount of house mites/grams of dust in ninety homes in three areas of Bogota (Ciudad Bolivar, Rafael Uribe Uribe and San Cristobal). Methods: the methodology was based upon collecting samples by vacuuming mattresses, pillows and floors. Works were conducted in thirty houses in such areas, having a total of ninety families and 270 dust samples. Results: per family they were compiled in the stated form specifying the amount of dust mites per gram of dust. Then, the collected data were analyzed through descriptive statistics and measures of central tendency. The most determinant species was found to be the Dermatophagoides pteronissynus with the highest percentage found in pillows (Ciudad Bolivar, 71. 32% ; Rafael Uribe Uribe, 69. 66%, and San Cristobal, 75%). However, mattresses and floors also showed a predominant percentage. Conclusions: the highest average of dust mites/grams of dust were found in the mattresses of Ciudad Bolivar (92.50) and San Cristobal (617.49), while Rafael Uribe Uribe showed to have the highest percentage on floors (36.59).